Critique of the Theory of Tajaddud-e-Amsāl (Renewal of the Forms) - Seyyed Mohammad Mousavi Baygi; Abbas Hakimzadeh (آموزه‌‌های فلسفه اسلامي, 2023)
Change and transformation among beings is an evident reality that anyone can observe in the world around them. Since these transformations are rulings of a particular degree of existence, their interpretation falls under the responsibility of general sciences such as philosophy and mysticism. Although the fact of change in beings is clear, various theories have been proposed regarding the manner in which these changes occur. One of these theories is the “Tajaddud-e-Amsāl (Renewal of the Forms)" with the meaning of the execution and creation of everything other than Allah (God) moment by moment, which has been proposed by mystics. Proponents of this theory claim not only to have witnessed this phenomenon but also attempt to prove it using Qur'anic verses like "Every day He is in a new state" or "Rather, they are in a new creation" and through some mystical principles such as the "non-repetition of divine manifestations." According to this theory, since the entire world, according to mystics, is a manifestation of the one truth (existence), this manifestation is annihilated every moment, and a new manifestation appears in its place. This research, which employs a critical-analytical approach, reveals that this theory faces significant challenges such as the destruction of personal unity, the lack of distinction between immaterial and material beings, and the collapse of individual unity in the afterlife.